Dialectics of Communication between Mother and Daughter in Susah Sinyal Film (Study of Descriptive Qualitative Content Analysis) - Istiati Dyah (Budapest International Research and Critics University, 2022)
Film has developed into a very popular medium because it does more than just provide entertainment. But it also has informative, persuasive, and educative elements in it. In Indonesia, the film industry has been so advanced, with many films of various genres. One of them is a comedy-drama film entitled Susah Sinyal, which is a film about family relationships that are so fluctuating and dynamic due to the many conflicts between the mother and daughter characters. This study uses a descriptive qualitative content analysis method that aims to examine the dialectic of communication that occurs in the Susah Sinyal film by using the elements contained in the Relational Dialectics Theory (RDT). RDT is a theory that explains that in interpersonal relationships, there are various contradictions and tensions that come from multivocality, or differences in interests and desires among the individuals involved. However, this multivocality can achieve unity and resolution if managed through good communication so that the existing contradictions will bring positive changes in the relationship concerned.